Short Communication: New record of wild banana (Musa balbisiana Colla) in West Kalimantan, Indonesia - ARI SUNANDAR (Biodiversitas Journal of Biological Diversity, 2017)
Sunandar A. 2017. Short Communication: New record of wild banana (Musa balbisiana Colla) in West Kalimantan, Indonesia. Biodiversitas 18: 1324-1330. Kalimantan Island (Indonesia) is part of the center of origin and diversity of wild bananas in Indo-Malesia region. West Kalimantan is one of province in Kalimantan Island. However, only a little information is available about diversity of wild bananas in West Kalimantan. The aims of this study were to study a possible new record of wild banana species in Nipah Panjang and Teluk Nibung Villages, Kubu Raya District and to describe its phenetic relationships among wild banana species based on morphological characters. By examination based on the morphological character, one species of wild banana was identified, i.e. Musa balbisiana found in Teluk Nibung Village (Local name: Pisang Klotok). However, we didn’t found any wild bananas in Nipah Panjang Village. M. balbisiana was a new record in West Kalimantan. Previously, M. balbisiana is widely distributed only in Java and Sulawesi. M. balbisiana was found in roadsides or backyards of residents in Teluk Nibung Village. Dendrogram of phenetic relationship showed that M. balbisiana from West Kalimantan had similarity with M. balbisiana from Sulawesi with coefficient of similarity 80%.